Answer:
A
Step-by-step explanation:
This is how I write
y=kx+m
but I have seen some write it like this:
y=mx+b
Well both of them are the same thing, I'll use the first one because I'm more comfortable with it.
y=kx+m
To find out what k
![k = \frac{y2 - y1}{x2 - x1}](https://tex.z-dn.net/?f=k%20%3D%20%20%5Cfrac%7By2%20-%20y1%7D%7Bx2%20-%20x1%7D%20)
So you first need to choose two points.
I'll go for (0,-5) and (2,0)
![k = \frac{0 - 5}{2 - 0}](https://tex.z-dn.net/?f=k%20%3D%20%20%5Cfrac%7B0%20-%205%7D%7B2%20-%200%7D%20)
![k = \frac{ - 5}{2}](https://tex.z-dn.net/?f=k%20%3D%20%5Cfrac%7B%20-%205%7D%7B2%7D%20)
Now you could insert k into the equation and it will look like this.
![y = \frac{ - 5}{2}x + m](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B%20-%205%7D%7B2%7Dx%20%2B%20m)
To find out what m is just pick one point and insert it into the equation. So if I pick (0,-5). 0=X therefore it should be replaced by x and -5=y therefore it should also be replaced by y.
![- 5 = \frac{ - 5}{2} \times 0 + m](https://tex.z-dn.net/?f=%20-%205%20%3D%20%20%5Cfrac%7B%20-%205%7D%7B2%7D%20%5Ctimes%200%20%2B%20m)
m=-5
Try it with another point to see if you get the same answer. this time I'll pick (-6,10)
![10= \frac{ - 5}{2} \times( - 6)+ m](https://tex.z-dn.net/?f=%2010%3D%20%20%5Cfrac%7B%20-%205%7D%7B2%7D%20%5Ctimes%28%20-%206%29%2B%20m)
m= -5
The equation will be y=-5/2x-5)